PDC Analysis of LLDPE-NR Nanocomposite for Effect of Moisture Absorption - N. A. M. Jamail; M. A. M. Piah; N. A. Muhammad; Q. E. Kamarudin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The properties of insulation have been improved by many research and the ability of nanocomposite material that composes the characteristic of improving electrical performance due to the addition of nanofiller into the based material gets serious attention. Polarization and Depolarization Current (PDC) measurement that has the ability to assess the condition of HV insulations with the initial periods after a DC step voltage application was favoured compared to other non-destructive monitoring techniques. This paper presents the works on moisture absorption in LLDPE-NR nanocomposite with different amount and percentage of nanofillers. The study of PDC level of the LLDPE-NR compound, filled with different amount of SiO2, TiO2 and MMT nanofiller using Polarization and Depolarization Current (PDC) measurement technique is the main objective of this research. These results show that sample A1 has the lowest polarization current value and sample B5 has the lowest depolarization current value.